Capital structure, corporate taxation and firm age - Michael Pfaffermayr; Matthias Stöckl; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2009)
This paper analyzes the relationship between corporate taxation, firm age and debt. We adapt a standard model of capital structure choice under corporate taxation, focusing on the financing and investment decisions a firm is typically faced with. Our model suggests that the debt ratio is positively associated with the corporate tax rate, and negatively with firm age. Further, we predict that the tax-induced advantage of debt is more important for older than for younger firms. To test these hypotheses empirically, we use a cross-section of 405,000 firms from 35 European countries and 126 NACE 3-digit industries. In line with previous research, we find that a firm's debt ratio increases with the corporate tax rate. Further, we observe that older firms exhibit smaller debt ratios than their younger counterparts. Finally, consistent with our theoretical model, we find a positive interaction between corporate taxation and firm age, indicating that the impact of corporate taxation on debt is increasing over a firm's life-time.
Keywords: H20; H32; G32; C31; 330; Corporate taxation; Capital structure; Firm age